PENGARUH EDUKASI GIZI MELALUI MEDIA VIDEO ANIMASI DAN POSTER TERHADAP CITRA TUBUH, PENGETAHUAN, DAN SIKAP GIZI SEIMBANG PADA SISWA SMAN 10 TANGERANG - Karina Ariella Pratiwi (2022)
Nutritional problems can be caused by a person's lack of information related to nutrition. Nutrition education can be one way to overcome nutritional problems that can change a person's knowledge. Education using posters and animated videos is a preventive way because it can facilitate the delivery of health. This research was conducted to determine the effect of nutrition education through animated video and poster towards body image, knowledge, and attitudes of balanced nutrition in students of SMAN 10 Tangerang. The method used in this research is Quasi Experimental with two group pre-test post-test designs. The sample in this study was 40 respondents who were divided into 2 groups, namely the poster group and the animated video group. The statistical test used is the Wilcoxon test and the Mann-Whitney test. The results showed that there was an effect of nutrition education using posters and animated videos on body image knowledge (p-value <0.05). The value of body image knowledge in the video animation group was higher than the poster group (p-value=0.019). So it can be concluded that animated video media is more effective in increasing body image knowledge compared to poster media.